The Right to Private Property in the Face of Taxes with Confiscatory Effects - Armijos González, Pedro Orlando (2023)
Confiscation in tax matters in the Ecuadorian Constitution is not strictly prohibited, only which properties suffer from when they are declared of public utility and are expropriated. Faced with this situation, the Constitutional Court recognizes the principle of non-confiscation, in tax matters, indicating that, although it has not been constitutionalized, the tax regime contains it, therefore, authorities are obliged to apply and respect it permanently. In this context, despite the fact that the right to private property is protected by the Constitution, there are numerous cases, mainly at the sectional level, where it is intended to collect excessive taxes that violate the right to property, directly ignoring the pronouncement of the Constitutional Court. The disrespect for taxpayers’ ability to pay, in the same way as their right to have their vital minimum exempt respected, places them on a negative status, since their real ability to contribute is not taken into account. In addition, they are also not given the option of satisfying their basic needs first but are demanded the payment of an excessive tax. Finally, it is necessary to point out that the core of the right to private property has three categories: use, enjoyment, and disposal, as this paper outlines the multilayered nature of this issue.